2004
DOI: 10.1037/0894-4105.18.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory and Perseveration in Verbal Fluency.

Abstract: Letter and semantic fluency tasks are often used in neuropsychological assessment and are sensitive to many conditions. Performance is assessed by correct responses and errors, including perseverations. Healthy young adults performed letter and semantic fluency tasks. One group performed these tasks in the conventional manner; 2 other groups performed them while maintaining memory loads. The memory loads consisted either of words from the same category as the fluency task or of words from a different category.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
2
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 38 publications
2
72
2
16
Order By: Relevance
“…Comparing the evidence, it was observed that both groups achieved a better performance in the semantic category ("animals") compared to the phonological test ("F"), which is in line with the findings of the other studies conducted in healthy individuals (18,21) . Although the PVF test allows a greater amount of words to be evoked, the SVF category follows a hierarchical organization in memory, having subcategories ("farm animals," "pets," "marine animals," "land animals," among others) and enabling a greater range of responses (22) . The literature states that, even in the phonological tasks, there is a tendency for word generation in streams, often generated by semantic relations (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the evidence, it was observed that both groups achieved a better performance in the semantic category ("animals") compared to the phonological test ("F"), which is in line with the findings of the other studies conducted in healthy individuals (18,21) . Although the PVF test allows a greater amount of words to be evoked, the SVF category follows a hierarchical organization in memory, having subcategories ("farm animals," "pets," "marine animals," "land animals," among others) and enabling a greater range of responses (22) . The literature states that, even in the phonological tasks, there is a tendency for word generation in streams, often generated by semantic relations (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in relation to verbal fluency, the available evidence suggests that the secondary activity needs to be particularly attention demanding-involving high executive load-before it disrupts retrieval. For instance, concurrent suppression (vocalization of a digit sequence) and concurrent memory load (serial retention of a digit sequence), significantly impair fluency, the effects of the latter task being particularly marked (Baddeley, Lewis, Eldridge, & Thomson, 1984; but see also Azuma, 2004;Rosen & Engle, 1997; Retrieval and Distraction 6 Troyer, Moscovitch & Winocur, 1997;Moscovitch, 1994). However, to date no study has shown fluency to be vulnerable to passively-processed concurrent material such as to-be-ignored sound.…”
mentioning
confidence: 99%
“…There is consensus that phonemic fluency is as heavily-weighted on executive processes as the semantic fluency task (if not more so) but is relatively free of semantic processing (Henry, Crawford, & Phillips, 2004). Phonemic fluency shares with semantic fluency many of the executive elements, but one component-the automatic process of activation spreading from the cued category name (Rosen and Engle, 1997, p. 224)-is qualitatively different: The task involves a more algorithmic, instance-based, search process based on abstract or novel rules and is thus not entirely semantic (Azuma, 2004; cf. Schwartz, Baldo, Graves, & Brugger, 2003).…”
mentioning
confidence: 99%
“…A korábbi kutatásokban a leggyakrabban a szavak számát vizsgálták (Benton és mtsai, 1976;Benton, 1968;Miller, 1984;Rosen, 1980;Benton és Hamsher, 1989;Troyer és mtsai, 1997;Hurks és mtsai, 2004;Hurks, Vles, Hendriksen, Kalff, Feron, Kroes, Van Zeben és Jolles, 2006, Troyer, 2000Mészáros, Kónya és Kas, 2011), illetve a hibák és perszeverációk számából következtettek az egyes neuropszichológiai károsodások meglétére (Azuma, 2004).…”
Section: áBra Az Egyes Munkamemória-komponensek éS a Végrehajtó Funkcunclassified
“…A második módszer, amit mi is használtunk a disszertációban bemutatott vizsgálataink során, az információk szisztematikus szerveződését tárja fel. Hagyományosan a teljesítmény mutatójaként leggyakrabban a helyesen generált szavak számát tekintik (Benton és Hamsher, 1976;Benton, 1968;Miller, 1984;Rosen, 1980;Benton és Hamsher, 1989;Hart, Smith és Swash, 1986;Gurd és Ward, 1989;Hanley, Dewick, Davies, Playfer és Turnbull, 1990;Paus, 1991;Crawford,Moore és Cameron, 1992;Pasquier, Lebert, Grymonprez és Petit, 1995), emellett a perszeverációk (ugyanannak a szónak a megismétlése a válaszadás folyamán) és hibák (az instrukciónak nem megfelelő kezdőbetűvel kezdődött válaszok) meglétéből illetve mértékéből próbálnak következtetni különböző neuropszichológiai eltérésekre és deficitekre (Lees és Smith, 1989;Crowe, 1992;Azuma, 2004;Henry és Crawford, 2004;Tröster, Salmon, McCullogh és Butters, 1989;Tröster, Warmflash, Osorio, Paolo, Alexander és Barr, 1995;Tröster, Fields, Testa, Paul, Blanco, Hames, Salmon és Beatty, 1998 …”
Section: A Verbálisfluencia-tesztek (Betű-és Szemantikusfluencia-teszunclassified